Bell's palsy syndrome: mimics and chameleons. Issue 6 (31st March 2016) - Fuller, Geraint; Morgan, Cathy
Abstract : In this article we will explore the mimics and chameleons of Bell's palsy and in addition argue that we should use the term 'Bell's palsy syndrome' to help guide clinical reasoning when thinking about patients with facial weakness. The diagnosis of Bell's palsy can usually be made on clinical grounds without the need for further investigations. This is because the diagnosis is not one of exclusion (despite this being commonly how it is described), a lower motor neurone facial weakness where all alternative causes have been eliminated, but rather a positive recognition of a clinical syndrome, with a number of exclusions, which are described below. This perhaps would be more accurately referred to a 'Bell's palsy syndrome'. Treatment with corticosteroids improves outcome; adding an antiviral probably reduces the rates of long-term complications.